Механізми узгодження економічних інтересів держави та підприємств: довгострокові наслідки радянського корпоративізму - Сливка, Т. О.; Небрат, В. В. (Київський національний університет імені Тараса Шевченка, 2025)
Актуальною проблемою забезпечення стійкості та розвитку економіки України є гармонізація інтересів підприємницького сектора, держави та суспільства. Історико-економічне дослідження має значний евристичний потенціал для пояснення природи й механізмів розходження цих інтересів. Метою статті є ретроспективний аналіз інституційної взаємодії держави і підприємств, зокрема, механізмів узгодження різнорівневих корпоративних інтересів у централізовано-плановій економіці радянського періоду та розкриття довгострокових наслідків економічної політики держави на мікрорівні. Охарактеризовано історичний феномен бюрократичного корпоратизму радянського періоду як симбіоз груп інтересів вищого менеджменту виробничих підприємств та державних чиновників виконавчої гілки влади. Виявлені такі довготривалі наслідки економічної політики держави: сформована в радянські часи система обмеженого доступу до ресурсів, яка дозволяла реалізовувати інтереси бюрократії в межах централізованого розподілу, була відтворена і розширена в процесі ринкової трансформації економіки; концентрація виробництва в централізованій економіці стала передумовою концентрації власності в період ринкових реформ; традиція державного патерналізму обумовила формування екстрактивної моделі великого бізнесу в Україні, її наслідками стали посилення економічних дисбалансів, прискорене руйнування основних фондів, нераціональне використання ресурсів, формування низькотехнологічної структури виробництва та експорту.

The current problem of ensuring the sustainability and development of the Ukrainian economy is the harmonization of the interests of the business sector, the state and society. Historical-economic research has significant heuristic potential for explaining the nature and mechanisms of these divergences of interests. A retrospective analysis of the institutional interaction between the state and enterprises, in particular the mechanisms for coordinating different levels of corporate interests in the centrally planned economy of the Soviet period, and the disclosure of the long-term consequences of the state's economic policy at the micro level are the goals of this article. The research methodology uses the concept of path dependence, the theory of interest groups, methodological approaches and theoretical provisions regarding the connection between formal and informal institutions, and the patterns of their reproduction. The historical phenomenon of bureaucratic corporatism of the soviet period is characterized. It was formed as a symbiosis of interest groups of top management of manufacturing enterprises and state officials of the executive branch of government. The following long-term consequences of the state's economic policy were identified: 1) the system of limited access to resources formed in Soviet times, which allowed the interests of the bureaucracy to be realized within the framework of centralized distribution, was recreated and expanded in the process of market transformation of the economy; 2) the concentration of production in a centralized economy became a prerequisite for the concentration of ownership during the period of market reforms. The system of Soviet state monopoly turned into a monopoly of corporations in the economy of Ukraine; 3) the tradition of state paternalism has led to the formation of an extractive model of big business in Ukraine. Its consequences have been the strengthening of economic imbalances, the accelerated destruction of fixed assets, the irrational use of resources, and the formation of a low-tech structure of production and exports.
Mechanisms for Harmonizing the Economic Interests of the State and Enterprises: Long-Term Consequences of the Soviet Corporatism
Keywords: корпоративні інтереси; управління підприємством; економічна історія; державний патерналізм; неформальні інститути; економічна влада бюрократії; концентрація власності; ефект колії; низькотехнологічна структура економіки; corporate interests; enterprise management; economic history; state paternalism; informal institutions; economic power of bureaucracy; property concentration; path dependence; low-tech structure of the economy